2015
DOI: 10.1088/2041-8205/803/1/l6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Flux Conservation in the Heliosheath Including Solar Cycle Variations of Magnetic Field Intensity

Abstract: In the heliosheath (HS), Voyager 2 has observed a flow with constant radial velocity and magnetic flux conservation. Voyager 1, however, has observed a decrease in the flow's radial velocity and an order of magnitude decrease in magnetic flux. We investigate the role of the 11 yr solar cycle variation of the magnetic field strength on the magnetic flux within the HS using a global 3D magnetohydrodynamic model of the heliosphere. We use time and latitude-dependent solar wind velocity and density inferred from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The inclusion of a time dependent solar wind with solar cycle variations would lead to an alternation between fast and slow solar wind at the poles, which would affect the ENA signal both in the polar regions near the termination shock and further back in the lobes. The solar cycle variations could also have an effect on the intensity of the solar magnetic field as shown in Michael et al (2015), which could have an effect on the collimation as well. Additionally, since the PUI density and temperature ratios used will directly affect the ENA flux, the particular method used to include these ratios may affect the ENA flux as well.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of a time dependent solar wind with solar cycle variations would lead to an alternation between fast and slow solar wind at the poles, which would affect the ENA signal both in the polar regions near the termination shock and further back in the lobes. The solar cycle variations could also have an effect on the intensity of the solar magnetic field as shown in Michael et al (2015), which could have an effect on the collimation as well. Additionally, since the PUI density and temperature ratios used will directly affect the ENA flux, the particular method used to include these ratios may affect the ENA flux as well.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of models (e.g., Pogorelov et al 2009Pogorelov et al , 2012Pogorelov et al , 2013Opher et al 2011Opher et al , 2012Opher & Drake 2013;Washimi et al 2011;Borovikov et al 2012;Fisk & Gloeckler 2013) describe the structure and dynamics in the heliosheath. Recent models by Provornikova et al (2013Provornikova et al ( , 2014 and by Michael et al (2015) predict the observed B and radial speeds at V1 and V2. Whang & Burlaga (1994;Whang et al 1995) followed the evolution of a GMIR through the supersonic wind and heliosheath and its interaction with the heliopause.…”
Section: Structure and Formation Of The Interaction Regionmentioning
confidence: 94%
“…Pogorelov et al (2009Pogorelov et al ( , 2012 showed that the decrease in the speed to V R  0 could be explained by a nonstationary three-dimensional model that included solar cycle variations. On the other hand, Provornikova et al (2013Provornikova et al ( , 2014 and Michael et al (2015), who considered solar cycle variations in an MHD model with boundary conditions near the Sun, predicted that the speed at V1 should be a constant. They interpreted the decrease in magnetic flux at V1 as a result of magnetic reconnection.…”
Section: Magnetic Flux Conservationmentioning
confidence: 99%
“…A number of models attempted to describe the evolution of the solar wind from 1 au, through the heliosheath, and beyond (Zank et al 1996;Baranov & Zaitsev 1998;Zank & Müller 2003;Liu et al 2007Liu et al , 2014Pogorelov et al 2012aPogorelov et al , 2013Opher et al 2011;Borovikov et al 2012;Opher 2012;Provornikova et al 2013Provornikova et al , 2014Fermo et al 2015;Michael et al 2015;Zirnstein et al 2016).…”
Section: Relationship Between the Magnetic Fields Observed In The Heliosheath And Magnetic Fields Observed In The Vlismmentioning
confidence: 99%